PENGARUH PROGRAM LITERASI TERHADAP MINAT MEMBACA PADA MUATAN BAHASA INDONESIA SISWA KELAS IV SDN 12 IX KOTO - Hader, Antik Estika; Ningsi, Pitri; Efendi, Raimon (Jurnal Tunas Pendidikan, 2023)
The research was conducted due to the problem of students' lack of interest in reading, especially in class IV SD N 12 IX Koto. The purpose of this study was to evaluate the effect of the literacy program on reading interest in Indonesian language lessons in fourth grade elementary school students. This study uses a quantitative approach to the type of experimental research. The sample of this research was 11 students of class IV SD N 12 IX Koto. A pretest-posttest design with only one group was used for the study. The results showed that the implementation of the literacy program had a positive impact on students' Indonesian learning achievement. There was an increase in the average score of Indonesian lessons from 67.55 to 81.18 after the implementation of the literacy program. students' ability and understanding of Indonesian also increased after the literacy program was implemented. the findings showed that the percentage of students who met the Minimum Completeness (KKM) increased from 4 (36%) to 9 (73%). Therefore, it can be concluded that the use of literacy programs has a positive effect on reading interest and increases Indonesian learning achievement in fourth grade students at SDN 12 IX KOTO.